2010
DOI: 10.1371/journal.pone.0013481
|View full text |Cite
|
Sign up to set email alerts
|

Glial Innate Immunity Generated by Non-Aggregated Alpha-Synuclein in Mouse: Differences between Wild-type and Parkinson's Disease-Linked Mutants

Abstract: BackgroundParkinson's disease (PD) is a progressive neurodegenerative disorder characterized pathologically by the presence in the brain of intracellular protein inclusions highly enriched in aggregated alpha-synuclein (α-Syn). Although it has been established that progression of the disease is accompanied by sustained activation of microglia, the underlying molecules and factors involved in these immune-triggered mechanisms remain largely unexplored. Lately, accumulating evidence has shown the presence of ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
82
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(88 citation statements)
references
References 83 publications
6
82
0
Order By: Relevance
“…Even though a study using monocytic THP-1 cell line (Klegeris et al, 2008) had shown modest increases in IL-1 and TNF- secretion levels after stimulation with A30P, A53T, or E46K Syn mutants compared to the Wt protein, there is a lack of a comprehensive study of the effect exerted by non-aggregated Syn, performed with primary cell cultures. With this in mind, we analysed the cytokine release profile of primary microglial cultures -which represesnts a more comparable physiological environment-after stimulation with Wt or the PD-linked Syn mutants (Roodveldt et al, 2010). Indeed, we found remarkable differences between the Syn variants in the interleukin and chemokine release profiles and significant effects on the microglial phagocytic capacity (Roodveldt et al, 2010).…”
Section: Syn-induced Microglial Activationmentioning
confidence: 98%
See 2 more Smart Citations
“…Even though a study using monocytic THP-1 cell line (Klegeris et al, 2008) had shown modest increases in IL-1 and TNF- secretion levels after stimulation with A30P, A53T, or E46K Syn mutants compared to the Wt protein, there is a lack of a comprehensive study of the effect exerted by non-aggregated Syn, performed with primary cell cultures. With this in mind, we analysed the cytokine release profile of primary microglial cultures -which represesnts a more comparable physiological environment-after stimulation with Wt or the PD-linked Syn mutants (Roodveldt et al, 2010). Indeed, we found remarkable differences between the Syn variants in the interleukin and chemokine release profiles and significant effects on the microglial phagocytic capacity (Roodveldt et al, 2010).…”
Section: Syn-induced Microglial Activationmentioning
confidence: 98%
“…A few investigations that explore the effects of non-aggregated Syn on the cytokine release profile of potentially relevant cells have been recently done using monocytic (Klegeris et al, 2008) or macrophage (Lee et al, 2009b) cell lines, and primary astrocyte (Klegeris et al, 2006) or microglial (Roodveldt et al, 2010;Su et al, 2009;Su et al, 2008) cultures. Indeed, we have observed a strong innate immune response in primary glial and microglial cell cultures elicited by exogenous, non-aggregated Syn (Roodveldt et al, 2010). Interestingly, a comparative study using unmodified aSyn has recently shown that exogenous non-aggregated Syn induces higher TNF-, IL-1 and ROS release levels than aggregated Syn in microglia (Lee et al, 2010).…”
Section: Syn-induced Microglial Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests other cells in the brain such as astroglia [11,17] . Moreover, unlike the endocytotic internalization of α-syn fibrils and oligomers, monomeric α-syn enters the cell through membrane transport (a non-endocytotic mechanism), and its internalization is much faster than that of the aggregated form [12] .…”
Section: Externalization and Internalization Of Aggregated α-Syn In Mmentioning
confidence: 99%
“…Missense mutation, overexpression, or gene damage of α-syn undoubtedly increases the probability of its aggregation. All of these conditions appear to contribute at least partially to familial and sporadic PD [17,18] .…”
Section: Impaired Intracellular Degradation Of α-Synmentioning
confidence: 99%